Pemanfaatan fasilitas bus rapid transit (BRT) Semarang bagi penyandang disabilitas - Rudianto (Journal of Gender Equality Disability Social Inclusion and Children, 2024)
Utilization of Bus Rapid Transit (BRT) facilities for people with disabilities is an important aspect in efforts to create public transportation that is inclusive and friendly to diverse communities. This research aims to analyze the extent to which BRT facilities can be utilized by people with disabilities and identify the challenges and opportunities faced in the utilization process. This research method involves field surveys, interviews, and qualitative data analysis. The research results show that although several BRT facilities have been designed taking into account the needs of people with disabilities, there are still obstacles in their use. Some of these obstacles include stop accessibility, bus stop designs that are not fully disability-friendly, as well as a lack of understanding and awareness on the part of BRT managers and general users regarding the needs of people with disabilities. On the other hand, this research also identified several opportunities to increase the use of BRT facilities by people with disabilities, including through the development of information and communication technology, active involvement of people with disabilities in the planning and evaluation process of facilities, as well as increasing training for BRT operators and officers in serving passengers. with special needs. It is hoped that this research can contribute to the development of more inclusive public transportation policies and planning, ensuring that BRT facilities not only meet technical standards but are truly accessible and utilized by all levels of society, including people with disabilities.